State and output-feedback shared-control for a class of linear constrained systems - Jiang,J; Astolfi,A (IEEE Transactions on Automatic Control, 2015)
This paper presents state and output feedback sharedcontrol algorithms for a class of linear systems in the presence of constraints on the output described by means of linear inequalities. The properties of the closed-loop shared-control systems are studied using Lyapunov arguments. Simulation results demonstrate the effectiveness of the algorithm.